KREATIFITAS SISWA SMK NEGERI 1 AMPEK ANGKEK DALAM PEMANFAATAN LIMBAH KAYU - Abdi Gustihardian; Yuniarti Munaf; Ranelis Ranelis (Institut Seni Indonesia Padangpanjang, 2023)
This research was conducted to increase student creativity in utilizing wood waste at SMK Negeri 1 Ampek Angkek, Agam Regency. The main problem in this research is that students tend to be more passive and less creative, so they are constrained in creating ideas to work on using wood waste. This study uses qualitative methods with active participation observation data collection techniques, interviews and documentation. The data analysis technique was carried out in a descriptive-interpretative manner. Improving student creativity in utilizing sawdust waste is carried out in several important stages, including; preparing materials and equipment, making designs/sketches, learning processes and being creative in making sawdust products decorative, functional and aesthetic. The results of the study show that measuring students' abilities can be seen based on their ability to design works, persistence in working on works and students' creativity in making works. Efforts made to increase student creativity are carried out by using varied learning media and displaying visual forms in the form of videos of the process of making wood products and photos of examples of wood waste products, training students' abilities in creating new ideas in choosing product forms.